Experimental inoculation of gilts with bovine viral diarrhea virus 2 (BVDV-2) does not induce transplacental infection - Araujo Pereira, Daniele [UNESP] (2018)
Bovine viral diarrhea virus (BVDV) belongs to the genus Pestivirus and can cause reproductive problems in cattle. However, there is still a lack of research to clarify its pathogenicity in different gestational periods of sows and its effects in neonates. In this study, 12 gilts divided into groups (G) were experimentally inoculated with the strain BVDV-2 (SV-253) oronasally at a dose of 106·85 TCID50; one group was inoculated 30 days before insemination (G0; n = 2), three groups were inoculated during gestation (first (G1; n = 2), second (G2; n = 3), third (G3; n = 3)), and a fourth was the control group (G4; n = 2). Samples of blood and nasal swabs from the gilts were collected every three days until delivery for a virus neutralization (VN) test, qRT-PCR, and blood count. On the day of delivery, 40% of the neonates were euthanized to obtain tissue and blood samples at necropsy for histopathology and qRT-PCR. The sows were seroconverted between 12 and 33 days after inoculation, and the virus was detected in the blood between 3 and 12 days and on the nasal swab between 6 and 24 days in the G0, G1, G2 and G3 sows but was not detected in piglet tissues, and no significant alterations were found through histopathology. The mean and standard deviation of the mean cycles (Cq) from blood (Cq = 34.87 ± 0.60) and nasal swab (Cq = 34.61 ± 0.87) samples were between 107 and 490 TCID50/ml. Transient infection was demonstrated with a low viral load, but transplacental infection was not possible in gilts.